Agricultural mechanization and structural transformation in Myanmar’s Ayeyarwady delta - Win, Myat Thida; Thinzar, Aye Mya (Michigan State University, 2018)
Agricultural mechanization is already well advanced in the village tracts surveyed, almost completely replacing the use of draft cattle. Economic reforms and the growth in the non-farm sector from 2011 have stimulated an ongoing process of structural transformation, in which labor is moving from agriculture to the more productive urban industrial and service sectors. Resultant rural labor shortages and increases in real wage rates have been major drivers of mechanization in agricultural sector, particularly from 2013 onwards. The declining real price of some types of machinery has contributed to the acceleration of this process. The increasing availability of financial services following reforms post-2011 is also likely to have accelerated the adoption of large-scale agricultural machinery, particularly from 2013 onwards. The rise of rental markets, especially for large-scale equipment (combine harvesters and four-wheel tractors), has further improved access to these machines for farmers with small and large landholdings alike.